PELATIHAN PEMBUATAN LILIN AROMATHERAPY DALAM PEMANFAATAN LIMBAH MINYAK JELANTAH DI DESA MRICAN - Ekayanti, Arta; Wardani, Adinda Kusuma; Winaryo, Anton; Rohani, Binti; Astuti, Erika Puji; Juwariyah, Hananda Luthfi; Karimah, Hasanah Ahlaqul; Dewi, Helen Candra Puspita; Nurfrendi, Imam Sa’id; Alfitri, Kaneisya Hokia; Setyawati, Shintya Ayu (LPPM UNIVERSITAS MUHAMMADIYAH MUARA BUNGO, 2024)
This study focuses on training in making aromatherapy candles using used cooking oil waste in Mrican Village, Jenangan District, Ponorogo Regency, East Java. The purpose of this activity is to provide innovative solutions to reduce environmental pollution due to waste disposal of used cooking oil and improve community welfare through entrepreneurship. This training involved PKK mothers from Mrican Village who were taught the process of refining used cooking oil and making aromatherapy candles directly. The implementation method of this activity was carried out by socializing the dangers of used cooking oil waste, practicing making aromatherapy candles from used cooking oil directly, and ending with a question and answer session. The results of this activity were that PKK mothers had knowledge and skills on how to utilize used cooking oil waste so that it can be reprocessed into a product with sales value such as aromatherapy candles. This training succeeded in raising awareness of the importance of recycling and managing household waste, as well as encouraging the creation of environmentally friendly creative businesses.